Effectiveness and potential mechanism of Jiawei-Xiaoyao-San for hyperthyroidism: a systematic review - Ma, Wenxin; Zhang, Xiaowen; Zhao, Ruotong; Tang, Yang; Zhu, Xiaoyun; Liu, Longkun; Xu, Mingyuan; Wang, Ge; Peng, Peiyue; Liu, Jianping; Liu, Zhaolan (Frontiers in Endocrinology, 2023)
Objectives To evaluate the effectiveness and potential mechanism of traditional Chinese medicine Jiawei-Xiaoyao-San (JWXYS) as an adjunct or mono- therapy for antithyroid drugs (ATDs) in the treatment of hyperthyroidism. Methods Eight databases and three trial registries were searched from inception until May 2023. Randomized controlled trials (RCTs) were included and meta-analysis was conducted using RevMan 5.4 and Stata 14.0. The Cochrane risk of bias (ROB) tool 1.0 and GRADE tool was used for quality appraisal. The findings from case reports using mono-JWXYS and pharmacological studies were summarized in tables. Results Thirteen RCTs with 979 participants were included. The majority of the included studies were assessed as high risk of bias in one ROB domain. Compared with ATDs, JWXYS plus ATDs resulted in lower free triiodothyronine (FT3) (MD = -1.31 pmol/L, 95% CI [-1.85, -0.76]; low-certainty), lower free thyroxine (MD = -3.24 pmol/L, 95% CI [-5.06, -1.42]; low-certainty), higher thyroid stimulating hormone (MD = 0.42 mIU/L, 95% CI [0.26, 0.59]; low-certainty), higher effectiveness rate of traditional Chinese medicine syndrome (RR = 1.28, 95% CI [1.08, 1.52]; low-certainty), lower goiter score (MD = -0.66, 95% CI [-1.04, -0.29]; very low-certainty), lower thyrotrophin receptor antibody (SMD = -0.44, 95% CI [-0.73, -0.16]; low-certainty) and fewer adverse events (AEs) (RR = 0.34, 95% CI [0.18, 0.67]; moderate-certainty). Compared with regular dosage of ATDs, JWXYS plus half-dose ATDs resulted in fewer AEs (RR = 0.24, 95% CI [0.10, 0.59]; low-certainty). Compared with ATDs in 1 trial, JWXYS resulted in higher FT3, lower goiter score and fewer AEs. Three case reports showed that the reasons patients sought TCM-only treatment include severe AEs and multiple relapses. Three pharmacological studies demonstrated that JWXYS restored Th17/Treg balance, lowered deiodinases activity, regulated thyroid cell proliferation and apoptosis, and alleviated liver oxidative stress in mouse or rat models. Conclusion JWXYS may enhance the effectiveness of ATDs for hyperthyroidism, particularly in relieving symptoms and reducing AEs. Mono-JWXYS is not recommended except in patients intolerant to ATDs. The findings should be interpreted with caution due to overall high risk of bias. Further pharmacological studies with more reliable models are needed. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023394923.